Respuesta :

Answer: OPTION D

Step-by-step explanation:

Given the functions f(x) and g(x) shown in the figure attached, you have that g(x)-f(x) means that you must subtract both functions.

Therefore, keeping this on mind, you have:

[tex]g(x)-f(x)=3x^{3}-x^{2}+7x-(x^{2}+3x+5)[/tex]

Now, you must distributive the negative sign that is in front of the parentheses and add the like terms. Then, you obtain:

[tex]g(x)-f(x)=3x^{3}-x^{2}+7x-x^{2}-3x-5\\g(x)-f(x)=3x^{3}-2x^{2}+4x-5[/tex]

Answer:

Answer is C

Step-by-step explanation:

F(x)=X^2+3x+5-G(x)= 3x^3-X^2+7x

(F-G(x))= -3x^3+2x^2-4x+5

ACCESS MORE